Tales of me: storytelling identity work, authenticity, and impression management during new CEOs’ work role transitions - Felix, Bruno; Santos, Renata dos; Teixeira, Aridelmo (Frontiers in Psychology, 2023)
This study aims to understand how new CEOs construct, revise, and maintain in their narrative, repertoire stories that represent their identity as it is associated with their new occupational role. For this purpose, we conducted a qualitative study using the Grounded Theory method, involving 47 CEOs from different sectors residing in Brazil. Our results allowed for the construction of a central category called Storytelling Identity Work, which refers to stories that individuals tell about themselves, and enable them to propose and redefine who they are during major life transitions. This paper seeks to explain: a) under what conditions this phenomenon tends to occur; b) what characterizes the success of Storytelling Identity Work and; c) what leads to the revision or retention of stories in the self. Our results show that storytelling identity work tends to be used by new CEOs during their transition period into the role, and when their new position involves higher levels of visibility and alteration of prestige levels in comparison to their previous position. They also suggest that storytelling identity work tends to be more successful when the stories are co-constructed and validated with other significant individuals and when they enable new CEOs to feel "sufficiently authentic" and "sufficiently impressive." Finally, we theorize that such feelings, along with a sense of coherence between the story being told and other narratives consciously or unconsciously being narrated by the interviewees throughout their lives, lead to the retention of the story within the individual's self. This article innovates by connecting the literature on personal storytelling with identity work and exploring processes that are not only useful during the process of transitioning into the role of new CEOs but also influence the constitution of the narrative repertoire and, consequently, the identity of these individuals.